Designing fitness aerobics classes in physical education of university students - Levitskaya A.N.; Ponomarev V.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to theoretically substantiate, develop a methodology and sets of exercises for female students doing fitness aerobics in physical education at a university and test their effectiveness in a pedagogical experiment. Methods and structure of the study. The study involved 50 first-year students of the Siberian Federal University. Using a random sampling method, the students were divided into experimental and control groups of 25 people. The experimental group did fitness aerobics during physical education, and the control group followed a traditional program based on general physical training. To determine the effectiveness of physical education classes based on the design of fitness aerobics in comparison with the traditional form of physical education, physical fitness indicators were taken: 2000 m run; 100m run; flexion and extension of the arms while lying down; standing long jump; lifting the body from a lying position in one minute. Results and conclusions. Based on the results of a year-long pedagogical experiment, the physical fitness indicators of the experimental and control groups were analyzed. The growth of the following indicators was analyzed: general endurance, speed endurance, strength indicators of the shoulder girdle, speed-strength indicators of the legs and strength indicators of the abdominal muscles. In all indicators of physical fitness, students from the experimental group engaged in physical education based on fitness aerobics outperformed students from the control group by an average of 17.6% (P<0.05). These results allow us to state the need to periodically include sets of exercises from fitness aerobics into the process of physical education to increase physical fitness indicators among female students in a yearly cycle.